Problems with Strontium Isotopic Proveniencing in Denmark? - Price, Douglas (Danish Journal of Archaeology, 2022)
A recent study by Thomsen and Andreasen (2019) has induced a negative reaction to the usefulness of strontium isotope proveniencing. Although there are higher strontium isotope values in the landscape of Denmark, Thomsen and Andreasen are not correct about the impact of this finding on studies of prehistoric mobility. Several case studies identify such “hotspots” in the landscape and help evaluate their consequences for identifying non-local individuals. In sum, (1) there are small areas of higher strontium isotope values in Denmark, (2) surface water is not a reliable proxy for baseline information on local strontium isotope sources, and (3) strontium isotope proveniencing remains a very useful method for identifying non-local individuals. Corrigendum! This article has been republished on 25 February 2022. In the new version, Fig. 3 was changed to remove unpublished samples. The editors.